OPINIONS OF EUROPEAN MANAGERS ON THE CHALLENGES OF TEAM MANAGEMENT IN MULTICULTURAL WORK ENVIRONMENTS - Knap-Stefaniuk, Agnieszka (Management and Administration Journal, 2024)
In contemporary companies, the knowledge and experience of both employees and managers significantly influence decision-making, operational effectiveness, and strategy implementation, especially in conditions of the continuously increasing role played by international cooperation. Multiculturalism is not only a common feature of companies which operate in the global market but also increasingly a key factor when it comes to people management. Although cultural diversity can bring many positive effects, it can also be a source of a range of problems. Thus it is so important for managers of culturally diverse teams to understand the essence of multiculturalism, to be able to manage cultural diversity skilfully, and to endorse values and adhere to principles which are highly relevant in multicultural work environments. The study presented in the article (individual in-depth interviews) was conducted among managers from six European countries. The main aim of the study was to identify challenges posed by multicultural work environments based on the opinions of managers who work with multicultural teams. The theoretical part of the article explains the concept of multiculturalism and presents multiculturalism in the context of management in contemporary work environments. The empirical part discusses the results of the interviews and the resulting conclusions. Undoubtedly, multiculturalism poses numerous challenges to managers in the area of people management, and the results of the study have confirmed that managers face considerable challenges in multicultural work environments (especially in the areas regarding managers’ factual knowledge on and preparation for the management of teams, the level of their cultural intelligence, communication, and employee motivation).